Improving Students' Learning Outcomes in Public Vocational High School by Implementing Problem-Based Learning with Scientific Approach - Tuwoso, Tuwoso (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
This study explored the effect of combining a scientific approach with problem-based learning on enhancing students' critical thinking skills. The scientific approach sought to direct learners to understand various materials scientifically from multiple sources. The quantitative study in the experimental design used the nonrandomized control group treated with pre-test post-test design. This study had 48 students who separated into two groups. The experimental group used a problem-based learning and scientific approach (PBL-SA), whereas the control group used a traditional learning approach. According to the findings, the average post-test score for the traditional learning group was 33.33, whereas the average post-test score for the PBL-SA group was 65.42. The traditional learning group had low scores, whereas the average achievement of students in the PBL-SA group increased from 42.08 to 65.42, indicating an improvement. The PBL-SA group outperformed the traditional learning group on the Basic Mechanical Engineering Design with a statistically significant difference.